Ectopic eruption of maxillary permanent first molars: Predictive factors for self‐corrected and impacted outcome. Issue 3 (18th December 2020) - Caliskan, Secil; Tuloglu, Nuray; Ozdemir, Canan; Kizilaslan, Sena; Bayrak, Sule
Abstract: Objective: The aim of this study was to describe the occurrence, angulation and mesialisation ratio of the ectopic eruption of the maxillary permanent first molar (PFM) and its correlation with the pathological resorption of maxillary primary second molar (PSM). Methods: This retrospective study was performed using the subsequent panoramic radiographs of 11.924 child patients aged 6‐10 years. Ectopic eruption status is categorised as self‐corrected and impacted types. To evaluate the differences between the two groups (self‐corrected and impacted), the angulation of PFM, mesialisation ratio of PFM, and degree of adjacent PSM root resorption were also assessed. The data were statistically analysed using ANOVA and chi‐square tests. Pearson correlation was used to analyse whether a quantitative relationship exists between PFM mesialisation ratio and PSM root resorption. Results: Ectopic eruption frequency was determined as 0.83%. The distribution of ectopic eruption according to gender shows a higher prevalence in males than females. In most cases of ectopic eruption, the eruption status was impacted. The impacted PFMs showed more negative vertical and positive horizontal angle between the PSM and PFM. There was no significant difference between eruption status and angles. Mesialisation ratio of impacted PFMs was significantly higher than self‐corrected PFMs. There was significant difference between the PFM mesialisation ratio and the degree of PSM root resorption. Conclusion: Even if eruption disturbances do not occur frequently, making an early diagnosis is important to begin treatment at an optimal time. Although the relationship between horizontal and vertical angles and the ectopic eruption pattern is controversial, it is one of the clinical determinants. The mesialisation ratio of the impacted type was significantly higher than the self‐corrected type. Self‐correction of PFM was reduced in PSM with grade III and IV root resorption.